Mandatory Drug offender Processing Data, 1986: Alaska, California, Iowa, Minnesota, Nebraska, New York, North Carolina, and Virginia ([Verlag nicht ermittelbar], 1992)
The National Consortium for Assessing Drug Control Initiatives, funded by the Bureau of Justice Assistance and coordinated by the Criminal Justice Statistics Association, collected drug offender processing data from eight states: Alaska, California, Iowa, Minnesota, Nebraska, New York, North Carolina, and Virginia. The purpose of the project was to track adult drug offenders from the point of entry into the criminal justice system (typically by arrest) through final court disposition, regardless of whether the offender was released without trial, acquitted, or convicted. These data allow researchers to examine how the criminal justice system processes drug offenders, to measure the changing volume of drug offenders moving through the different segments of the criminal justice system, to calculate processing time intervals between major decision-making events, and to assess the changing structure of the drug offender population. For purposes of this project, a drug offender was defined as any person who had been charged with a felony drug offense. The data are structured into six segments pertaining to (1) record identification, (2) the offender (date of birth, sex, race, ethnic origin), (3) arrest information (date of arrest, age at arrest, arrest charge code), (4) prosecution information (filed offense code and level, prosecution disposition and date), (5) court disposition information (disposition offense and level, court disposition, final disposition date, final pleading, type of trial), and (6) sentencing information (sentence and sentence date, sentence minimum and maximum). Also included are elapsed time variables. The unit of analysis is the felony drug offender.